Early Immunogenetic Markers For Predicting Food Allergy Development In Children: Clinical And Molecular Approaches (Texas Journal of Medical Science, 2025)
Food allergy (FA) is a rapidly increasing immunopathological condition in childhood, often developing during the first years of life when immune regulation, epithelial barrier integrity and microbiota composition are still maturing. Early detection is essential to prevent progression toward atopic dermatitis, asthma, and allergic rhinitis. Immunogenetic markers—including cytokine signatures, epithelial alarmins, filaggrin gene mutations and microRNA profiles—represent promising early predictors of FA